Genetic engineering to enhance microalgal-based produced water treatment with emphasis on CRISPR/Cas9: A review - Hassanien, Alaa; Saadaoui, Imen; Schipper, Kira; Al-Marri, Sara; Dalgamouni, Tasneem; Aouida, Mustapha; Saeed, Suhur; Al-Jabri, Hareb M. (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the increased demand for and regional variability of available water resources, along with sustainable water supply planning, have driven interest in the reuse of produced water. Reusing produced water can provide significant economic, social, and environmental benefits, particularly in water-scarce regions. Therefore, efficient wastewater treatment is a crucial step prior to reuse to meet the requirements for use within the oil and gas industry or by external users. Bioremediation using microalgae has received increased interest as a method for producing water treatment for removing not only major contaminants such as nitrogen and phosphorus but also heavy metals and hydrocarbons. Some research publications reported nearly 100% removal of total hydrocarbons, total nitrogen, ammonium nitrogen, and iron when using microalgae to treat produced water. Enhancing microalgal removal efficiency and growth rate, in the presence of such relevant contaminants is of great interest to many industries to further optimize the process. Genetic modification is a novel approach to further enhancing algal capabilities and phytoremediation of wastewater. A comprehensive description of using genetically engineered microalgae for wastewater bioremediation is discussed in this review. This article also reviews random and targeted mutations as a method to alter microalgal traits to produce strains capable of tolerating various stressors related to wastewater. Other methods of genetic engineering are discussed, with sympathy for CRISPR/Cas9 technology. This is accompanied by the opportunities, as well as the challenges of using genetically engineered microalgae for this purpose.